Effect of subretinal injection on retinal structure and function in a rat oxygen-induced retinopathy model - Becker, Silke (Mol Vis, 2017)
PURPOSE: Subretinal injections are used to deliver agents in experimental studies of retinal diseases, often through viral vectors. However, few studies have investigated the effects of subretinal injections alone on the structure and function of the healthy or diseased retina, particularly in models of oxygen-induced retinopathy (OIR). We report on the effects of subretinal injections in a rat OIR model, which is used to study mechanisms of retinopathy of prematurity. METHODS: Within 6 h of birth, neonatal rat pups were exposed to repeated cycles of oxygen between 50% and 10% O(2) every 24 h for 14 days and subsequently moved to room air. On postnatal day 8 (P8), animals were treated in both eyes with advancement of the injection needle into the vitreous (pilot-treated) or with a subretinal PBS injection (sPBS-treated) or were left untreated (untreated). Additional control animals were exposed to microscope light after eyelid opening only (light-treated). Retinal fundus images were recorded on P26. Areas of the avascular retina and intravitreal neovascularization were determined in flat mounted retinas stained with isolectin B4 on P32. Retinal function of the respective eyes was assessed with the Ganzfeld electroretinogram (ERG) on P31 or P32 and with focal ERG in the central retina on P28 or P29. The thickness of the retinal layers was measured with spectral domain optical coherence tomography (OCT) on P30 and in opsin- and TO-PRO 3-stained retinal cryosections from pups euthanized on P32. Two sections were analyzed in each pup. For each section, three images of three different locations were analyzed accounting for 18 thickness measurements per pup. RESULTS: Compared to untreated animals, the avascular area of the retina was greater in the pilot-treated (p<0.05) and sPBS-treated eyes (p<0.01), and the sPBS-treated eyes had a greater avascular retinal area compared to the pilot-treated eyes (p<0.01). The intravitreal neovascular area was larger in the sPBS-treated eyes compared to the untreated eyes (p<0.01). The outer nuclear and outer segment layers were thinner in the pilot- (p<0.01) and sPBS-treated eyes (p<0.05) compared to the untreated eyes as measured with OCT and immunohistochemical staining of the retinal cryosections. Compared to the untreated eyes, the amplitudes of the scotopic a- and b-waves in the Ganzfeld ERG were reduced in the pilot-treated eyes (p<0.001 and p<0.01, respectively), but only the a-wave was reduced in the sPBS-treated eyes (p<0.001). The a-wave amplitude in the focal ERG was reduced in the pilot- and sPBS-treated eyes, and no difference was seen in the b-wave amplitude between any of the groups. There was no difference between the light-treated and untreated eyes in the areas of the avascular retina or intravitreal neovascularization or Ganzfeld or focal ERG. CONCLUSIONS: Pilot injections alone without injection into the subretinal space resulted in an increased avascular retinal area, reduced thickness of the photoreceptors, and reduced ERG function compared to the untreated animals. Although subretinal PBS injections further increased the areas of avascular retina and intravitreal neovascularization and resulted in similar retinal thinning compared to the pilot treatment, inner retinal function was improved, as evidenced by higher Ganzfeld b-wave amplitudes. Differences in the Ganzfeld and focal ERGs may indicate that the peripheral retina is more susceptible to remote beneficial effects from potential protective mechanisms induced by subretinal injection. This study stresses the importance of appropriate controls in experiments with subretinal delivery of agents.